school buildings’ requirements to achieve school curricula’ objectives from the point of view of teachers of primary education - a field study in primary schools of the south of Medea - - Ghidi, Samir; Achoui, Abdelhamid (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
This study aims to identify the availability of the school building requirements to achieve the objectives of the school curricula in terms of location, design, school equipment, school activity, Safety and Health at School from the point of view of the primary education teachers, and to verify significant differences in the level of assessment of these requirements according to the nature of the school building (modern, old) and the number of floors. To achieve these objectives, a questionnaire was designed to collect the data from a sample of 112 teachers in 21 primary schools in the administrative districts of Ain Boucif and Chellalat El Adhaoura in the south-east of Media. The results revealed the availability of the school building requirements needed to achieve the school curricula goals in terms of location, design, school equipment, safety and health at school, while the requirements of the academic activity necessary to achieve these school curricula are not available, from teachers’ points of view.